2017
DOI: 10.1016/j.rbmo.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Counselling considerations for chromosomal mosaicism detected by preimplantation genetic screening

Abstract: The evolution of preimplantation genetic screening (PGS) for aneuploidy to blastocyst biopsy and more sensitive 24-chromosome screening techniques has resulted in a new diagnostic category of PGS results: those classified as mosaic. This diagnosis presents significant challenges for clinicians in developing policies regarding transfer and storage of such embryos, as well as in providing genetic counselling for patients prior to and following PGS. Given the high frequency of mosaic PGS results and the wide rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 20 publications
1
39
0
1
Order By: Relevance
“…Patients considering the transfer of mosaic embryos should undergo comprehensive genetic counseling, reviewing the possible risks and outcomes related with the transfer of such embryos (31). Confirmation of the fetal karyotype by invasive prenatal diagnosis, preferably amniocentesis, should also be suggested for any ensuing pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients considering the transfer of mosaic embryos should undergo comprehensive genetic counseling, reviewing the possible risks and outcomes related with the transfer of such embryos (31). Confirmation of the fetal karyotype by invasive prenatal diagnosis, preferably amniocentesis, should also be suggested for any ensuing pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Such a phenomenon is relatively common in human preimplantation embryos, affecting 15%-90% of cleavage-stage embryos and 30%-40% of blastocyst-stage embryos (25)(26)(27)(28)(29). Mosaicism arises from mitotic segregation errors occurring after fertilization via a variety of mechanisms, including anaphase lag, mitotic nondisjunction, inadvertent chromosome demolition, and premature cell division before DNA duplication (26,30,31). The percentage of abnormal cells within a euploid/aneuploid mosaic embryo is influenced by the cleavage stage in which the chromosomal segregation error occurs.…”
mentioning
confidence: 99%
“…When copy number falls between disomy and aneusomy, mosaicism is inferred. Ratios >80% or <20% can not be detected in a five-cell sample, but it is generally agreed that results beyond those ranges can be considered to be aneuploid or euploid, respectively (6,12). However, it has been suggested that under certain conditions, the finding of mosaicism may be artifactual or limited by a high false positive rate (11,34).…”
Section: Discussionmentioning
confidence: 99%
“…Contributing to the controversy is the fact that there are several presentations of mosaicisms in TE cells, including whole-chromosome, segmental (or partial), and complex. It has been proposed that some mosaic embryos may be more suitable to transfer than others, as a function of the specific chromosomes that are affected and the degree of mosaicism defined by the percentage of aneuploid cells (7,12).…”
mentioning
confidence: 99%
“…While such prioritization schemes make sense in the case of meiotic abnormalities—the consequences of which are well described—their utility may be limited for mosaic embryos given the current state of knowledge. Indeed, mosaic aneuploidies involving nearly every chromosome can be compatible with live birth [92], but are associated with a range of clinical disorders [93]. …”
Section: Consequences Of Mosaicism For Embryonic Developmentmentioning
confidence: 99%